Ginseng Modern Aspects of the Famed Traditional Medicine - Hano, Christophe; Chen, Jen-Tsung (IntechOpen, 2022)
Ginseng is the most well-known Chinese medicine as well as one of the most used herbal medicines. It has a wide range of medical and pharmacological uses. This book provides an up-to-date critical view of the botanical description and complexity of ginseng, including its phytochemistry, traditional and biotechnological production systems, traditional usage, current applications, and future directions for the development of ginseng compounds as effective medicinal agents. It is a useful resource for academicians, scientists, students, and industry professionals interested in traditional medicine and ginseng.